The Effect of Job Insecurity on Turnover Intention Through Work Satisfaction in Employees of PT. Telkom Access Singaraja - Komang Krisna Heryanda (Universitas Pendidikan Ganesha, 2019)
This study aimed at examining the effect of (1) job satisfaction mediating the effect of job insecurity on turnover intention, (2) job insecurity on job satisfaction, (3) job insecurity on turnover intention, (4) job satisfaction on turnover intention. The method of data collection was done by observation, interviews and questionnaires by using a Likert scale. The analysis technique used was path analysis (path anaylsis) with the SPSS 17.0 for windows program. The analysis shows that (1) job satisfaction was able to mediate partially the effect of job insecurity on turnover intention, (2) job insecurity had a negative and significant effect on job satisfaction, (3) job insecurity had a positive and significant effect on turnover intention, (4) satisfaction work had a negative and significant effect on turnover intention.